Deaf people in the criminal justice system : selected topics on advocacy, incarceration, and social justice - Guthmann, Debra; Lomas, Gabriel I.; Paris, Damara Goff; Martin, Gabriel A. (Gallaudet University Press, 2021)
"This volume illuminates the unique challenges faced by deaf people when they are arrested, incarcerated, or navigating the court system"--